Fenomena Hijab Dalam Bisnis Kuliner Di Kota Medan - Marzuti Isra; Sri Sudiarti; Isnaini Harahap (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2018)
This study aims to describe about the use of hijab to women who work in culinary business Medan City. This research uses qualitative method whose data is descriptive analytical. The objects of this research are owners and female workers at the Bika Ambon Zulaikha and Bolu Meranti outlets. The research is using qualitative method with descriptive analytic data and collection by interviewing, observing and documenting techniques. The results of the study show that (1) Working with women workers is a policy applied by culinary investors for the purpose of implementing marketing management strategies in attracting the largest Muslim consumers in Medan and maintaining clean and hygienic environment for all culinary products. (2) Awareness of the veil of every female worker which are an ideological awareness and understanding long before work, find awareness and understanding of hijab after work also the awareness and understanding of the hijab is limited as the head cover to maintain the cleanliness of culinary products. (3) Hijab also contributes in building the perception of Islamic consumers to shop at culinary outlets. That Islamic consumers have the confidence and convenience of hygienic and halal guarantees when shopping for culinary at outlets whose workers use the hijab.